2005
DOI: 10.1111/j.1365-2125.2005.02533.x
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian approach for population pharmacokinetic modelling of sirolimus

Abstract: AimsTo explore a Bayesian approach for the pharmacokinetic analysis of sirolimus concentration data arising from therapeutic drug monitoring (poorly informative concentration-time point design), and to explore possible covariate relationships for sirolimus pharmacokinetics. MethodsSirolimus concentration-time data were available as part of routine clinical care from 25 kidney transplant recipients. Most samples were taken at or near the trough time point at steady state. The data were analyzed using a fully co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 34 publications
8
52
2
Order By: Relevance
“…In adults and children, sirolimus clearance has been reported to be associated with patient age 18-20 . Dansirikul and colleagues reported sirolimus clearance was inversely related to age in 25 adult renal transplant patients 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults and children, sirolimus clearance has been reported to be associated with patient age 18-20 . Dansirikul and colleagues reported sirolimus clearance was inversely related to age in 25 adult renal transplant patients 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In adults and children, sirolimus clearance has been reported to be associated with patient age 18-20 . Dansirikul and colleagues reported sirolimus clearance was inversely related to age in 25 adult renal transplant patients 18 . Similarly, Schachter and colleagues reported the sirolimus half-life to be shorter in children compared to adult data (10-24 hours vs 49-70 hours, respectively) based on their analysis of 24 sirolimus pharmacokinetic profiles in 13 pediatric renal transplant patients 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Sirolimus has low bioavailability (14% on average) and a long terminal elimination half‐life of ~62 h 7 . Studies in transplant patients have demonstrated marked interindividual pharmacokinetic variability, resulting in the widespread use of therapeutic drug monitoring based on whole blood concentrations 8 , 9 , 10 , 11 , 12 , 13 …”
mentioning
confidence: 99%
“…There are several publications regarding the pharmacokinetics of sirolimus in transplant patients, although none have explicitly incorporated the nonlinear pharmacokinetic characteristics into a mixed‐effects population model 8 , 9 , 10 , 11 , 12 . Jiao et al .…”
mentioning
confidence: 99%
“…Although an inverse relationship was found between SRL clearance and age in a population pharmacokinetic study of 25 kidney transplant recipients, patients aged N50 years in this study only made up 25% of the total sample size [80]. With the dramatic increase in the number of elderly transplant recipients in the last decade, more pharmacokinetic studies of mammalian target of rapamycin (mTOR) inhibitors with sufficient number of elderly transplant patients are needed, so as to better understand the role of age in drug variability.…”
Section: Mammalian Target Of Rapamycin Inhibitorsmentioning
confidence: 70%